Analisis Kebijakan Dalam Penanganan Dampak Serangan Orangutan (Pongo pygmaeus) Terhadap Tanaman Acacia sp. pada Hutan Tanaman Industri di PT. "˜XX"™ Kalimantan Timur - Habibi, Habibi; Rumanta, Maman; Kunda, Rony Marsyal (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Acacia sp. is widely cultivated in Indonesia's Industrial Plantation Forests (HTI), but orangutan attacks pose a significant threat to its sustainability. If not addressed, these disturbances can lead to substantial losses in Acacia cultivation, reducing the supply of industrial raw materials and hindering economic opportunities for local communities reliant on HTI development. This research aims to identify effective policy scenarios to mitigate the impact of orangutan attacks while ensuring the protection of these legally safeguarded primates. Utilizing the Analytic Hierarchy Process (AHP), insights were gathered from five experts through questionnaires and interviews, with data analyzed using Expert Choice 11 software. The research focused on PT. 'XX" Pengadan Village, Karangan District, East Kutai Regency, East Kalimantan. Based on this research, it was found that a stakeholder commitment approach is vital for managing orangutan interactions. Prioritizing the provision, management, and enrichment of conservation areas can help minimize attacks and support both orangutan conservation and the sustainability of Acacia sp. plantations. This balanced strategy aims to secure habitats for orangutans while safeguarding local livelihoods and promoting sustainable HTI practices.